2006
DOI: 10.1021/es0618189
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Prions in Soil:  Detergent Extraction of PrP from Soils

Abstract: The transmissible spongiform encephalopathies (TSEs) are caused by infectious agents whose structures have not been fully characterized but include abnormal forms of the host protein PrP, designated PrP(Sc), which are deposited in infected tissues. The transmission routes of scrapie and chronic wasting disease (CWD) seem to include environmental spread in their epidemiology, yet the fate of TSE agents in the environment is poorly understood. There are concerns that, for example, buried carcasses may remain a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 31 publications
6
66
0
Order By: Relevance
“…Prions can persist in soils for years (Seidel et al, 2007;Brown & Gajdusek, 1991) and binding of PrP TSE by soil particles may maintain prions near the soil surface, thereby increasing animal exposure (Johnson et al, 2006;Cooke et al, 2007;Ma et al, 2007). Soil particle-associated agents are infectious orally (Seidel et al, 2007;Johnson et al, 2007).…”
mentioning
confidence: 99%
“…Prions can persist in soils for years (Seidel et al, 2007;Brown & Gajdusek, 1991) and binding of PrP TSE by soil particles may maintain prions near the soil surface, thereby increasing animal exposure (Johnson et al, 2006;Cooke et al, 2007;Ma et al, 2007). Soil particle-associated agents are infectious orally (Seidel et al, 2007;Johnson et al, 2007).…”
mentioning
confidence: 99%
“…Different minerals bind prions with different binding capacity, quartz < kaolinite < Mte-Ca < Mte-Na, 31 and mineral particle size specific surface area also change binding capacity. Cooke et al 27 have shown that soils with similar textures can exhibit remarkably different protein recoveries, and explained this discrepancy by a difference in mineralogy and/or soil pH. Our studies with infectious prions have shown that soils with different mineralogical composition can vary in prion binding capacities (Fig.…”
Section: Prion Interactions With Different Soil Compoundsmentioning
confidence: 60%
“…Different cations affect height of the interlayer space and proteins associated with the interlayer areas of expandable clays (e.g., smectites) potentially decreasing their bioavailability. 49 Cooke et al 27 found lower recovery of recPrP in the presence of soil cations, a finding related to the strong interactions between clay particles and exchangeable cations. Soil solution composition may, in addition to pH, change the binding capacity of prions to whole soils.…”
Section: Soil Organic Mattermentioning
confidence: 97%
See 1 more Smart Citation
“…The N-domain has been shown to affect PrP aggregation, 92 and evidence suggests the N-domain might play a role in sorption to soils. 68,70,73,74,76 Therefore, both full-length and truncated prions should be used to study environmental fate.…”
Section: Routes Of Entry Occurrence and Detection In The Environmentmentioning
confidence: 99%